2006
DOI: 10.1016/j.ijid.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thin needle aspiration biopsy in the diagnosis and management of vertebral osteomyelitis (VO)

Abstract: Phylogeny of the genus Nocardia based on reassessed 16S rRNA gene sequences reveals underspeciation and division of strains classified as Nocardia asteroides into three established species and two unnamed taxons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 3 publications
4
29
0
Order By: Relevance
“…In this study, we obtained a similar result to previous studies in that antibiotic exposure prior to microbiologic diagnosis was associated with negative outcome of culture (7,10,15). We also analyzed the impact of previous antibiotics in a quantitative manner: if there were 4 or more days of antibiotic exposure, the chance of obtaining positive microbiologic cultures was significantly reduced.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In this study, we obtained a similar result to previous studies in that antibiotic exposure prior to microbiologic diagnosis was associated with negative outcome of culture (7,10,15). We also analyzed the impact of previous antibiotics in a quantitative manner: if there were 4 or more days of antibiotic exposure, the chance of obtaining positive microbiologic cultures was significantly reduced.…”
supporting
confidence: 75%
“…Some factors are related to the results of microbiologic diagnosis of PVO (3), and among them, an effect of prior antibiotic exposure has been reported in some studies (6,9). Several reports have suggested that prior exposure has a negative effect on microbiologic diagnosis (7,10,15), but others suggest that this is not the case (12). All of these studies had limitations, such as small sample size, heterogeneous patient populations that included tuberculous vertebral osteomyelitis and postoperative vertebral osteomyelitis, and failure to consider duration of antibiotic exposure.…”
mentioning
confidence: 99%
“…Twelve studies with agreement and 13 studies with disagreement were retrieved for review in full published reports. A total of 11 studies met the inclusion criteria for our review, of which seven studies had complete data to be included in the meta-analysis [29][30][31][32][33][34][35]. We attempted to contact the authors of all 11 studies that met the inclusion criteria to obtain missing information and verify abstracted data.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Prior antibiotic exposure has been reported in some studies to have a negative effect on microbiologic diagnosis (2)(3)(4)(5). In view of this, it is recommended that, for clinically stable patients, biopsy be delayed until at least 48 h after the last antibiotic has been administered (6).…”
mentioning
confidence: 99%